2016
DOI: 10.1080/02640414.2016.1159714
|View full text |Cite
|
Sign up to set email alerts
|

Observing the coach-created motivational environment across training and competition in youth sport

Abstract: Adopting an integrated achievement goal (Nicholls, J. G. (1989). The competitive ethos and democratic education. Cambridge, MA: Harvard University Press.) and self-determination theory (Deci, E. L., & Ryan, R. M. (2000). The "what" and "why" of goal pursuits: Human needs and the self-determination of behavior. Psychological Inquiry, 11, 227-268. doi:10.1207/S15327965PLI1104_01) perspective as proffered by Duda, J. L. (2013). (The conceptual and empirical foundations of empowering coaching: Setting the stage fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
85
0
5

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 71 publications
(92 citation statements)
references
References 39 publications
2
85
0
5
Order By: Relevance
“…This would give more information about the coaching climates, if girls/women and boys/men perceive coaching differently or if the gender differences are caused by the coach. Further, it would be interesting to figure out whether the athletes under the same coach were consistent with the reported coaching climate they belonged or does the coach use more or less disempowering or empowering coaching in training compared to competitions (see Smith, Quested, Appleton, & Duda, 2017). Therefore, it would be interesting to follow the same athletes if their burnout levels stay the same, decreases or even increases over time in different coaching climates.…”
Section: Future Directionsmentioning
confidence: 99%
“…This would give more information about the coaching climates, if girls/women and boys/men perceive coaching differently or if the gender differences are caused by the coach. Further, it would be interesting to figure out whether the athletes under the same coach were consistent with the reported coaching climate they belonged or does the coach use more or less disempowering or empowering coaching in training compared to competitions (see Smith, Quested, Appleton, & Duda, 2017). Therefore, it would be interesting to follow the same athletes if their burnout levels stay the same, decreases or even increases over time in different coaching climates.…”
Section: Future Directionsmentioning
confidence: 99%
“…More needs to be studied about the intersection between coach efficacy and prophecies. Coaches may have good intentions to behave and create desirable climates, but lack of teaching skills or efficacy could dictate how athletes perceive reality (Smith, Quested, Appleton, & Duda, 2016a;Werthner & Trudel, 2006).…”
Section: Discussionmentioning
confidence: 99%
“…One study observed that as the level of competition increases in school basketball, coaches and players also increase in their emphasis on winning [32]. Increased pressure to have a winning team may result in negative coaching behaviors, neglect of players' personal development, and encouragement of unsportsmanlike conduct [4] [33] [34] [35]. When teams are competing at higher competitive levels, evidence has shown that coaches are more likely to provide players with feedback that is focused on performance outcomes as opposed to mastery outcomes [32].…”
Section: Level Of Competition and Sportsmanshipmentioning
confidence: 99%